Association between serum ferritin and hypertension according to the working type in Korean men: the fifth Korean National Health and nutrition examination survey 2010–2012 - Lee, Dong-Hoon (Ann Occup Environ Med, 2018)
BACKGROUND: Several studies suggest that serum ferritin concentrations reflect systemic inflammation, and high ferritin levels can increase the risk of hypertension in adult men. Shift work is also known to increase the risk of hypertension; however, there has been no study about the relationship between serum ferritin levels and the prevalence of hypertension according to the working type. METHODS: This cross-sectional study included 4,442 male participants (3,651 daytime workers and 791 shift workers) who participated in the fifth Korean National Health and Nutrition Examination Survey. Hypertension was defined as a systolic blood pressure greater than or equal to 140 mmHg, a diastolic blood pressure greater than or equal to 90 mmHg or the current use of antihypertensive medications regardless of blood pressure values. For the statistical analyses, serum ferritin levels were reclassified into quartiles, and complex sample analyses were used to evaluate the relationship between serum ferritin levels and the prevalence of hypertension according to the working type in this study. RESULTS: Serum ferritin and shift work were positively associated with the prevalence of hypertension. The effect of interaction was above multiplicative. When compared to participants in the lowest serum ferritin quartile, the odds ratio for hypertension for participants in the highest serum ferritin quartile was 1.372 (1.027–1.833) in daytime workers and 2.009 (1.042–3.873) in shift workers after adjustment. CONCLUSIONS: The prevalence of hypertension increased as ferritin levels increased in individuals, especially in shift workers.